The Authority of Notary as Public Official in The Making of Land Deed and Auction Minutes Deed According to The Law Number 30 of 2004 on Notary - Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2014)
Birth of Law No. 30 of 2004 on Notary, regarded as the beginning of reforms in the field of notary. A notary who previously carried out its duties based on the Dutch heritage regulations Reglement op Het Notaris Ambt in Indonesie (Stb. 1860:3) was started feels aware of its existence by the government. However, one of the impact of these laws is the extension of the authority of the notary to make the auctions minutes deed and the land deed, but as it is known in advance, making auctions minutes deed is the authority of the auction official, and make the land deed is the land deed official authority (known as PPAT ). Based on Vendu Reglement (VR), only authorized officials that can make auctions minutes deed, and if the notary push him to make it, then the power of the deed will degrade into privately made deed because it is not made by the competent authority. As with the land deed, authorized officials to make the land deed is PPAT, but the authority specified in Article 2 paragraph (2) of Government Regulation No. 37 of 1998 on Land Deed Official. Therefore, the Notary can make land deed, on condition not including the deed contained in that Article 2 paragraph (2). How To Cite: Multazam, M. (2014). The Authority of Notary as Public Official in The Making of Land Deed and Auction Minutes Deed According to The Law Number 30 of 2004 on Notary. Rechtsidee, 1(2), 147-162. doi:http://dx.doi.org/10.21070/jihr.v1i2.94